Kathleen Gyssels, Kanaté Dahouda. « René Maran » - Fianco, Fabiana (Il Tolomeo, 2022)
Compte rendu de Gyssels, K. ; Dahouda, K. (éds) (2021). « René Maran ». Études caribéennes, 8, décembre. https://doi.org/10.4000/etudescaribeennes.23125.